Mecánica de la Fractura Aplicada a Ejes de Molinos de Caña de Azúcar - Rodríguez Pulecio, Sara; Coronado Marín, John Jairo; Arzola de la Peña, Nelson (Ingeniería, 2004)
In this article a method based on the Fracture Mechanics is presented for the calculation of the critical crack size and the life prediction of the mill top shafts of the sugar mills, with semielliptic and circumferential cracks. The calculations were carried out to the top shaft of the first mill in a Sugar Mill, but it can be applied in particular to any other case. Due to the presence of a multiaxial stress field it is necessary to use an equivalent stress intensity factor in the equation of Paris. The inspection interval required to avoid a fatigue failure of these elements was obtained. The calculation of residual life and maximum crack size was carried out in the area of the journal diameter change nearest to the square coupling. In this location the 25% of the failures were reported.